PENDIDIKAN BUDI PEKERTI ( Integrasi Nilai Moral Agama dengan Pendidikan Budi Pekerti ) - Su’dadah Su’dadah (Jurnal Kependidikan, 2014)
National educational orientations that tend to ignore the development of value dimension have inflicted students both individually and collectively. The problem that arises is that the students will know much about anything but they are lack of system of values, attitudes, interests and positive appreciation of what they know. The students will experience an unbalanced intellectual development compared to their maturity of personality, wherein this condition can bring out a figure who is less concerned with the surrounding environment and susceptible to distortion of value. As a result, the students will practice moral offense easily, because the value system that should become a benchmark for standardized everyday behaviors is not so sturdy. By reflecting on the limited efforts of the educational institutions to equip the students with moral values nowadays, a number of people committed to providing character education. Character education as a part of religious education aims to develop values, attitudes and behaviors of students who bring out noble characters. Orientasi pendidikan Nasional yang cenderung melupakan pengembangan dimensi nilai, telah merugikan peserta didik secara individual maupun kolektif. Tendensi yang muncul adalah, peserta didik akan mengetahui banyak tentang sesuatu, namun ia menjadi kurang memiliki sistem nilai, sikap,minat maupun apresiasi secara positif terhadap apa yang diketahui. Anak akan mengalami perkembangan intelektual tidak seimbang dengan kematangan kepribadian sehingga melahirkan sosok spesialis yang kurang peduli dengan lingkungan sekitarnya dan rentan mengalami distorsi nilai, sebagai dampaknya, peserta didik akan mudah tergelincir dalam praktik pelanggaran moral karena sistem nilai yang seharusnya menjadi standar dan patokan berperilaku sehari-hari belum begitu kokoh.Bercermin pada keterbatasan upaya lembaga pendidikan dalam membekali nilai-nilai moral peserta didik selama ini telah mengilhami munculnya komitmen dari sejumlah kalangan untuk memberikan pendidikan budi pekerti. Pendidikan budi pekerti sebagai bagaian yang memperkaya pendidikan agama bertujuan untuk mengembangkan nilai, sikap dan prilaku siswa yang memancarkan akhlak mulia / budi pekerti.